Answer:
Choice B is the answer.
Explanation:
We have given a quadratic equation.
3x² + 15 = –6x
3x²+6x+15 = 0
We have to find the solution of above equation.
Taking 3 common from above expression, we have
3(x²+2x+5) = 0
x²+2x+5 = 0
From above equation, a = 1,b = 2 and c = 5
x = (-b±√b²-4ac ) / 2a is quadratic formula to solve equations.
Putting values in above formula ,we have
x = (-2±√(2)²-4(1)(5) ) / 2(1)
x = (-2±√4-20 ) / 2
x = (-2±√-16) / 2
x = (-2±√-1√16) / 2 ∵ i = √-1
x = (-2±4i) / 2
x = 2(-1±2i) / 2
x = -1±2i
Hence, the solution of given equation is -1±2i.